Cangfudaotan decoction inhibits mitochondria-dependent apoptosis of granulosa cells in rats with polycystic ovarian syndrome - Jiang, Xiao-lin; Tai, He; Xiao, Xuan-si; Zhang, Shi-yu; Cui, Shi-chao; Qi, Shu-bo; Hu, Dan-dan; Zhang, Li-na; Kuang, Jin-song; Meng, Xian-sheng; Li, Shun-min (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is a universal endocrine and metabolic disorder prevalent in reproductive aged women. PCOS is often accompanied with insulin resistance (IR) which is an essential pathological factor. Although there is no known cure for PCOS, cangfudaotan (CFDT) decoction is widely used for the treatment of PCOS; nevertheless, the underlying mechanism is not clear. In this study, 40 Sprague-Dawley (SD) rats (female) were randomized to 4 groups, namely the control group, PCOS group, PCOS+CFDT group, and PCOS+metformin group. The rats in the control group were fed a normal-fat diet, intraperitoneally injected with 0.5% carboxymethyl cellulose (CMC, 1 mL/kg/d) for 21 days and orally given saline (1 mL/kg/d) for the next 4 weeks. The rats in the PCOS group, PCOS+CFDT group, and PCOS+Metformin group were fed a high-fat diet (HFD) and intraperitoneally injected with letrozole (1.0 mg/kg) for 21 days. During this period, we recorded the body weight, estrous cycles, and rate of pregnancy in all rats. We also observed the ovarian ultrastructure. Blood glucose indices, serum hormones, and inflammatory factors were also recorded. Then, we detected apoptotic and mitochondrial function, and observed mitochondria in ovarian granular cells by transmission electron microscopy. We also detected genes of ASK1/JNK pathway at mRNA and protein levels. The results showed that CFDT alleviated pathohistological damnification and apoptosis in PCOS rat model. In addition, CFDT improved ovarian function, reduced inflammatory response, inhibited apoptosis of granular cells, and inhibited the operation of ASK1/JNK pathway. These findings demonstrate the occurrence of ovary mitochondrial dysfunction and granular cell apoptosis in PCOS. CFDT can relieve mitochondria-dependent apoptosis by inhibiting the ASK1/JNK pathway in PCOS rats.